The impact of management accounting information and the moderating role of cloud computing on decision making in SMEs: research in Vietnam / Dao Nhat Minh and Pham Ngoc Toan - Minh, Dao Nhat; Toan, Pham Ngoc (UiTM Press, 2024)
Using the resource-based view of the firm (RBV) theory, this study examined the relationship between management accounting information and decision-making in small and medium-sized enterprises (SMEs) in Vietnam. The study also explored the moderating role of cloud computing in this relationship. Analyzing data from a sample of 184 SMEs in Vietnam, the results showed that management accounting information enhanced decision-making in these enterprises. All four dimensions of management accounting information—scope, timeliness and frequency of reporting, aggregation, and integration—affect decision-making within SMEs at different levels. Furthermore, if an enterprise adopts cloud computing, a technology which helps people share data and work together no matter where they are, it will increase the strength of this relationship. The results of this research will provide both evidence and motivation for Vietnamese SMEs to adopt management accounting and cloud computing. This will help them make optimal management and business decisions, as a ramification.